Nicotine Replacement Therapy in Dental Settings: An Exploratory Survey in Bangalore City, India - Sharma, Gaurav (Addict Health, 2016)
BACKGROUND: Smoking and other forms of tobacco use remain the most significant worldwide public health problem. The dental practice is being identified as potential location for smoking cessation activity. Nicotine replacement therapy (NRT) promotes the chances of tobacco cessation, however, evidence related to prescription of the NRT in dental settings is lacking. This study aimed to assess and compare the attitudes, practices, beliefs, and barriers in prescribing NRT for tobacco cessation among dental interns and post-graduates (PGs). METHODS: For a cross-sectional survey among 232 participants from 10 dental colleges in Bangalore, India, a 21-item questionnaire was developed: 11-item based on attitudes and practices toward tobacco cessation and 10-items regarding scope and challenges in prescribing NRT. The data were analyzed using descriptive statistics, chi-square test, and test of proportions. FINDINGS: Majority of participants reported ongoing tobacco cessation activity in their college. Statistically significant difference was found between interns and PGs for items related to tobacco cessation practice (assisting, providing follow-up visit). Regarding NRT, significant differences were seen for items related to practice (assisting, assessing motivation for NRT), belief (not an appropriate activity for dentist, a valuable resource, increase in quit attempts) and barriers (bitter taste, cost, and fear of addiction) (P < 0.050). The majority of the PGs suggested cessation center followed by health care workers and pharmacists for the provision of subsidized nicotine gums. CONCLUSION: Favorable practices and beliefs are seen regarding the prescription of NRT among interns and PGs although differences exist. Time, cost, and taste emerged as major barriers.